Gene expression profiles identify key factors in inflammatory odontoblastic dental pulp stem cell differentiation via TNFα/C5L2 - Irfan, Muhammad; Kim, Ji Hyun; Sreekumar, Sreelekshmi; Chung, Seung (Frontiers in Genetics, 2025)
IntroductionInflammation is a complex host response to harmful infections or injuries, playing beneficial and detrimental roles in tissue regeneration. Notably, clinical dentinogenesis associated with caries development occurs within an inflammatory environment. Reparative dentinogenesis is closely linked to intense inflammation, which triggers the recruitment and differentiation of dental pulp stem cells (DPSCs) into the dentin lineage. Understanding how inflammatory responses influence DPSCs is essential for elucidating the mechanisms underlying dentin and pulp regeneration.MethodsGiven the limited data on this process, a broad approach is employed here to understand better the complex mechanisms involved and identify downstream signaling targets. This study investigates the role of inflammation and the complement receptor C5L2 in the odontoblastic differentiation of DPSCs and the associated transcriptomic changes using poly-A RNA sequencing (RNA-seq). RNA-seq techniques provide insight into the transcriptome of a cell, offering higher coverage and greater resolution of its dynamic nature.ResultsFollowing inflammatory stimulation, DPSCs exhibit significantly altered gene profiles, including marked up-regulation of key odontogenic genes, highlighting the critical role of inflammation in dentinogenesis. We demonstrate that TNFα-treated, odontoblast-like differentiating DPSCs, under C5L2 modulation, show differentially expressed gene profiles and transcriptomic changes.ConclusionBeyond quantifying gene expression, RNA-seq data also enable the discovery of novel transcripts, the identification of alternatively spliced genes, and the detection of allele-specific expression. The data presented may offer new avenues for experimental approaches to uncovering pathways in dentinogenesis by identifying specific transcription factors and gene profiles.